Lung metastases in low‐risk gestational trophoblastic neoplasia: a retrospective cohort study. (20th December 2019) - Frijstein, MM; Lok, CAR; van Trommel, NE; ten Kate‐Booij, MJ; Massuger, LFAG; van Werkhoven, E; Short, D; Aguiar, X; Fisher, RA; Kaur, B; Sarwar, N; Sebire, NJ; et al.
Abstract : Objective: Presence of lung metastases in low‐risk gestational trophoblastic neoplasia (GTN) is generally considered not to influence prognosis. However, in a recent study in the Netherlands, GTN patients with lung metastases had a higher recurrence rate and more disease‐specific deaths compared with patients without metastases. The aim of the present study was to validate these findings in a different country. Design: Historical cohort study. Setting: Charing Cross Hospital, United Kingdom. Population: A total of 1040 low‐risk GTN patients treated with methotrexate (MTX) between 2002 and 2016 were identified: 65 with lung metastases (group 1) and 975 without metastases (group 2). Methods: Baseline characteristics, MTX resistance, survival and recurrence rates were recorded and compared between both groups. Main outcome measures: MTX resistance, recurrence rate and survival. Results: The occurrence of MTX resistance and median number of MTX courses to achieve remission was significantly higher in patients with lung metastases than patients without metastases (60% versus 38.9%, P = 0.001; and nine versus six courses, P < 0.001). All choriocarcinoma patients ( n = 4) with lung metastases developed MTX resistance. The recurrence rate was also higher in group I (9.2% versus 2.7%; P = 0.012). Disease‐specific survival was 100% in both groups. Conclusions: The presence of lung metastases at the start of MTX therapy is associated with increased incidence of MTX resistance and recurrence in low‐risk GTN without affecting overall survival, which remains 100%. However, individuals with low‐risk choriocarcinoma with lung metastases are likely to become resistant to MTX and primary multi‐agent chemotherapy should be considered. Tweetable abstract: The presence of lung metastases appears to increase the risk of recurrence in low‐risk GTN, but does not affect overall cure rates and survival. Tweetable abstract: The presence of lung metastases appears to increase the risk of recurrence in low‐risk GTN but does not affect overall cure rates and survival.